The p‐Orbital Delocalization of Main‐Group Metals to Boost CO2 Electroreduction. (8th November 2018) - He, Sisi; Ni, Fenglou; Ji, Yujin; Wang, Lie; Wen, Yunzhou; Bai, Haipeng; Liu, Gejun; Zhang, Ye; Li, Youyong; Zhang, Bo; Peng, Huisheng
Abstract: Enhancing the p‐orbital delocalization of a Bi catalyst (termed as POD‐Bi) via layer coupling of the short inter‐layer Bi−Bi bond facilitates the adsorption of intermediate *OCHO of CO2 and thus boosts the CO2 reduction reaction (CO2 RR) rate to formate. X‐ray absorption fine spectroscopy shows that the POD‐Bi catalyst has a shortened inter‐layer bond after the catalysts are electrochemically reduced in situ from original BiOCl nanosheets. The catalyst on a glassy carbon electrode exhibits a record current density of 57 mA cm −2 (twice the state‐of‐the‐art catalyst) at −1.16 V vs. RHE with an excellent formate Faradic efficiency (FE) of 95 %. The catalyst has a record half‐cell formate power conversion efficiency of 79 % at a current density of 100 mA cm −2 with 93 % formate FE when applied in a flow‐cell system. The highest rate of the CO2 RR production reported (391 mg h −1 cm 2 ) was achieved at a current density of 500 mA cm −2 with formate FE of 91 % at high CO2 pressure.